The association between community solidarity and adoption of public health preventive measures during the COVID-19 pandemic in a cross-sectional, multi-national sample - Jill Murphy; Michelle Sarah Livings; Martin Wong; Junjie Huang; Wanghong Xu; Andrés Caicedo; María Belen Arteaga; Harry H. X. Wang; Pramon Viwattanakulvanid; Erlinda C. Palaganas; Maria de Jesus Medina Arellano; Gil Soriano; et al. (PLoS ONE, 2025)
Background Few studies have examined the association between community solidarity and health-related behaviors. This study investigates solidarity in navigating challenges during the COVID-19 pandemic. Methods We used cross-sectional data from a multi-national survey of 1,346 respondents to examine (1) factors relating to feelings of solidarity, and (2) associations between solidarity and public health preventive behaviors. Results More than half (53.1%) of participants expressed feelings of solidarity; they were more likely to be aged 30 years or over, employed full-time, and residing in Eastern economies. We found a statistically significant association between positive feelings of solidarity and three of five COVID-19 prevention behaviors (social distancing, skipping an event, and masking in public). Those who reported previous influenza vaccination were also more likely to adopt these behaviors. Discussion The findings underscore the potential of fostering community solidarity to enhance prosocial actions amid widespread emergencies.